1969
DOI: 10.1113/jphysiol.1969.sp008854
|View full text |Cite
|
Sign up to set email alerts
|

Post‐tetanic potentiation at the neuromuscular junction of the frog

Abstract: SUMMARY1. Post-tetanic potentiation (PTP) was studied at the neuromuscular junction of the frog. The magnitude and time course of PTP was dependent on the number of stimuli in the tetanus, rather than on the frequency or duration of the tetanus. At low temperature the maximum amplitude of PTP was unchanged, but the time course was prolonged.2. The magnitude and time course of PTP was accounted for quantitatively by estimated changes in the fraction of transmitter released per stimulus. 4. It is concluded that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
110
0

Year Published

1972
1972
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(129 citation statements)
references
References 17 publications
19
110
0
Order By: Relevance
“…However, in contrast to the greatly increased testing EPPs measured 1 sec after the train at low quantal content, at normal quantal content, the EPP amplitudes dropped to a level that was below the control level, indicating that depression was present. From this depressed value, the testing EPP amplitudes then rose above the control level over time, suggesting that one or more of the slower decaying process that increase transmitter release during the train were obscured by depression immediately after the train, giving rise to classical posttetanic potentiation (Rosenthal, 1969;Magleby, 1973b;Zucker and Regehr, 2002). The depression may reflect a depletion of the RRP of synaptic vesicles during the train with recovery thereafter and perhaps also a decrease in the number of release sites (Takeuchi, 1958;Thies, 1965;Lass et al, 1973;Regehr and Stevens, 2001;Zucker and Regehr, 2002).…”
Section: Depression Dominates the Response Immediately After The Condmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to the greatly increased testing EPPs measured 1 sec after the train at low quantal content, at normal quantal content, the EPP amplitudes dropped to a level that was below the control level, indicating that depression was present. From this depressed value, the testing EPP amplitudes then rose above the control level over time, suggesting that one or more of the slower decaying process that increase transmitter release during the train were obscured by depression immediately after the train, giving rise to classical posttetanic potentiation (Rosenthal, 1969;Magleby, 1973b;Zucker and Regehr, 2002). The depression may reflect a depletion of the RRP of synaptic vesicles during the train with recovery thereafter and perhaps also a decrease in the number of release sites (Takeuchi, 1958;Thies, 1965;Lass et al, 1973;Regehr and Stevens, 2001;Zucker and Regehr, 2002).…”
Section: Depression Dominates the Response Immediately After The Condmentioning
confidence: 99%
“…Such short-term synaptic plasticity has been divided into processes of synaptic enhancement that increase transmitter release and synaptic depression (D) that decrease release. Components of enhancement include facilitation, augmentation (A), and potentiation (P), with time constants of Ͻ1 sec, ϳ7 sec, and tens of seconds to minutes, respectively (Mallart and Martin, 1967;Rosenthal, 1969;Magleby and Zengel, 1976a;McNaughton, 1982;Poage and Zengel, 1993). Components of depression include very fast, fast, and slow components with time constants of recovery of Ͻ0.5 sec, ϳ6 sec, and tens of seconds to minutes, respectively (Takeuchi, 1958;Magleby, 1973b;Dittman and Regehr, 1998;Wu and Betz, 1998;Stevens and Wesseling, 1999b;Wesseling and Lo, 2002) In this report, we study the interaction between augmentation and the fast (ϳ6 sec) component of depression to determine whether augmentation continues to enhance transmitter release when depression dominates the response.…”
Section: Introductionmentioning
confidence: 99%
“…Depletion of the releasable transmitter store explains many of the features of short-term depression at several synapses (Liley and North, 1953;Elmqvist and Quastel, 1965;Rosenthal, 1969;Kusano and Landau, 1975), however, at other synapses, changes in the presynaptic spike waveform (Dunlap and Fischbach, 1978;Klein and Kandel, 1980;Augustine, 1990;Sabatini and Regehr, 1997), inactivation of the presynaptic calcium current (Forsythe et al, 1998;Patil et al, 1998), or the inhibitory action of neuromodulators on presynaptic calcium channels (Yawo and Chuhma, 1993;Scanziani et al, 1997) may all contribute to the observed depression.…”
Section: Mechanisms Underlying Depression and Recovery At The Feti-flmentioning
confidence: 99%
“…The most clearly established of these is, of course, transmitter release (Katz & Miledi 1967, Douglas 1968. The biosynthesis of certain neurotransmitters is also regulated by calcium ion (Patrick & Barchas 1974), as is the number of quanta of transmitter released per nerve impulse (Rosenthal 1969, Klein & Kandel 1980.…”
Section: Synapsin Imentioning
confidence: 99%